Impact of clouds on the estimation of daily evapotranspiration from MODIS-derived instantaneous evapotranspiration using the constant global shortwave radiation ratio method. Issue 5 (19th March 2019) - Jiang, Yazhen; Tang, Ronglin; Jiang, Xiaoguang; Li, Zhao-Liang
ABSTRACT: Upscaling instantaneous evapotranspiration (ET), retrieved at a specific satellite overpass time, to a daily scale is a key issue in drought monitoring, water resource management, and climate change study. The constant global shortwave radiation ratio method, which maintains a constant ratio of incoming global shortwave radiation to ET during the diurnal cycle, is reported to be robust when temporally upscaling instantaneous ET. However, this temporal upscaling method is typically used on clear-sky days. This study aims to evaluate cloud effects on the constant global shortwave radiation ratio method for extrapolating instantaneous ET from Moderate Resolution Imaging Spectroradiometer and ancillary data to daily scale at the Yucheng station in China. Partly cloudy-sky (clear during satellite transit) and clear-sky days were selected using measured downward global shortwave irradiances; each partly cloudy-sky had a hypothetical clear-sky counterpart. Then, daily ET was estimated by extrapolating the instantaneous ET using the constant global shortwave radiation ratio method under clear-sky, partly cloudy-sky, and hypothetical clear-sky conditions. The results showed that (a) upscaled ET for clear-sky days had a bias of −4.3 W m −2 and a root mean square error (RMSE) of 14.5 W m −2, and upscaled ET on partly cloudy-sky days had a bias of −7.8 W m −2 and an RMSE of 18.9 W m −2, with more serious underestimations under partly cloudy-sky conditions and (b) daily ET obtained under partly cloudy-sky conditions were reduced due to cloud effects comparing with that under hypothetical clear-sky conditions.